2018
DOI: 10.4236/cn.2018.104011
|View full text |Cite
|
Sign up to set email alerts
|

Latency Aware and Service Delay with Task Scheduling in Mobile Edge Computing

Abstract: In a traditional Mobile Cloud Computing (MCC), a stream of data produced by mobile users (MUs) is uploaded to the remote cloud for additional processing throughout the Internet. Though, due to long WAN distance it causes high End to End latency. With the intention of minimize the average response time and key constrained Service Delay (network and cloudlet Delay) for mobile users (MUs), offload their workloads to the geographically distributed cloudlets network, we propose the Multi-layer Latency Aware Workloa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…All studies considered the energy and latency objectives during problem formulation and met the applications' Quality of Service requirements. Li et al [13][14][15] and Ying Wah et al [16] suggested energy, latency and cost-aware workload assignments in the distributed mobile edge/fog/cloudlet based cloud network. These studies solved the workload assignment based on NP-Hard scheduling heuristics and meta-heuristics.…”
Section: Related Workmentioning
confidence: 99%
“…All studies considered the energy and latency objectives during problem formulation and met the applications' Quality of Service requirements. Li et al [13][14][15] and Ying Wah et al [16] suggested energy, latency and cost-aware workload assignments in the distributed mobile edge/fog/cloudlet based cloud network. These studies solved the workload assignment based on NP-Hard scheduling heuristics and meta-heuristics.…”
Section: Related Workmentioning
confidence: 99%
“…However, still the centralized failure of any service affects the entire system. An e-agriculture and a body area sensor aware network based on SOA architecture was suggested and studied in [7,8]. The goal was to optimize the service process with minimum end to end latency of the applications while offering 24/7 services with the robot and faultless services.…”
Section: Related Workmentioning
confidence: 99%
“…However, they did not consider the resource-constraint limitation of applications. The study [7] surveyed fog cloud aware healthcare system for blood-pressure patients which required 24/7 services to monitor their data. The goal was to maximize service efficiency and minimize the latency of the applications.…”
Section: Related Workmentioning
confidence: 99%
“…Many healthcare monitoring system suggested to offer different services to the patients. Many existing studies [6][7][8][9][10] suggested different pricing model for healthcare applications such as E-Blood-Pressure, E-Blood Analysis, EEG, and ECG and so on. Every provider rent services based on different pricing model such as on-demand, on-reserve, and spot-instants [11].…”
Section: Introductionmentioning
confidence: 99%